What is propaganda? - Doeden, Matt (2020)
"Introduce readers to the concept of propaganda by analyzing examples from the past and present. This approachable overview includes tips on how to spot propaganda and how to respond to fake news"--
What is propaganda? -- Propaganda in history -- Propaganda and social media -- Spotting propaganda -- Fake news toolkit.
Includes bibliographical references and index.
Ages 8-11.
Grades 4-6.
Keywords: Propaganda -- Juvenile literature; Fake news -- Juvenile literature; Propaganda